(untitled) (GnosisWisdom, 2023)
The Journal of Scientific and Technological Research and Innovation GnosisWisdom, presents Vol.3, No 1 (2023) is a peer-reviewed publication managed through the Open Journal System. Its objective is worldwide dissemination, in its electronic version, it publishes original works on SOCIAL SCIENCE topics that preserve a character of originality, utility, scientific and technological relevance; that contribute new knowledge about theoretical or practical aspects in the different areas of knowledge.